PENGARUH PENERAPAN GOOD GOVERNMENT GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN (Studi pada Badan Pengelola Keuangan dan Aset Daerah Kota Kendari) - Sari, Ika Maya; Tamrin, Nur Arvah (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACT The purpose of the research is knowing the effect of the application of Good Government Governance and Human Resource Competency to Information Quality Financial Statements at the Financial Management Board and Asset Kendari, which can be viewed either parsial and simultan. The methods of data analysis used in this research is descriptive analysis method and multiple linear regression analysis method. The method of data collection use is the method of questionnaires that as many as 30 people of all staff involved in the preparation of the Local Government Finance Report at the Financial Management Board and Asset Kendari. However, just as many as 26 questionnaires can be processed.The results of this study showed that partially Good Government Governance significant effect to Information Quality Financial Statements and Human Resource Competency significant effect to Information Quality Financial Statements. Simultaneously, Good Government Governance and Human Resources Competency significant effect to Information Quality Financial Statements. This study also shows the coefficient of determination for Good Government Governance and Human Resource Competency to Information Quality Financial Statements of R2 = 0.694. The figure has meaning that the contribution of the variables X1 and X2 to Y is 69.4% and the remaining 30.6% is influenced by other factorsKeywords : Good Government Governance, Human Resource Competency, and Information Quality Financial Statements